2016
DOI: 10.1016/j.ttbdis.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and annotation of the salivary gland transcriptome of Rhipicephalus appendiculatus male and female ticks during blood feeding

Abstract: Tick secretory proteins modulate haemostasis, inflammation and immune responses of the host and are attractive recombinant anti-tick vaccine candidates. Yet, many of the proteins have not been characterised due to the limited sequence availability for ticks and other arthropods for homology-based annotation. To address this limitation, we sequenced the salivary glands of the economically important adult male and female Rhipicephalus appendiculatus ticks during feeding. The quality filtered Illumina sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 97 publications
(140 reference statements)
8
56
0
Order By: Relevance
“…Based on these results, we predict many more tick PIs are as yet undiscovered, primarily from one of the big three families: I2, I4 and I8. Though limited by the fact that transcripts in this study may not have been found due to technical and not biological reasons, our analysis of A. americium transcriptomes showed all PI families were always present, (with the exception of I35), but also supported previous in silico , semi-quantitiative and quantitative RT-PCR data showing differential expression of specific PIs within families [49, 5159], between the sexes, tissues, and throughout feeding. It is not possible to study all 1,595 tick PIs in a reasonable time frame, therefore this study provides a prioritization template for selecting suitable anti-tick vaccine and/or pharmacologically relevant targets.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Based on these results, we predict many more tick PIs are as yet undiscovered, primarily from one of the big three families: I2, I4 and I8. Though limited by the fact that transcripts in this study may not have been found due to technical and not biological reasons, our analysis of A. americium transcriptomes showed all PI families were always present, (with the exception of I35), but also supported previous in silico , semi-quantitiative and quantitative RT-PCR data showing differential expression of specific PIs within families [49, 5159], between the sexes, tissues, and throughout feeding. It is not possible to study all 1,595 tick PIs in a reasonable time frame, therefore this study provides a prioritization template for selecting suitable anti-tick vaccine and/or pharmacologically relevant targets.…”
Section: Discussionsupporting
confidence: 88%
“…We found and analyzed 1,595 non-redundant putative PI sequences across 26 ixodid tick species. In A. americanum we found evidence to support previous findings of a time-dependent PI expression in salivary glands [49, 51] coined as “sialome switch” [52], however our analyses provide evidence of time-dependent PI expression throughout tick tissues. Additionally, our global analysis differentiated tick PI families that are likely redundant or non-redundant, as well as PIs that are conserved across tick species and that may regulate pathways essential in all ticks.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, knowledge about the vital molecular constituents of ticks, such as genes and/or proteins, have become the target of several studies (CASTRO et al, 2016;CHMELAŘ et al, 2016;DÍAZ-MARTÍN et al, 2015;HEEKIN et al, 2013;KOTSYFAKIS et al, 2015;PERNER et al, 2016;RIBEIRO et al, 2017;XU et al, 2016). These studies have sought to ascertain and understand the roles of the molecules involved in the tick-host or tick-pathogen relationship.…”
Section: Introductionmentioning
confidence: 99%
“…DNA sequencing technologies, together with bioinformatics tools, allow a broad view of the probable protein constituents of a tissue, by isolating the messenger RNA repertoire and sequencing of the cDNA (complementary DNA), leading to an increasing knowledge of the putative molecules expressed by a tissue, such as, salivary gland and midgut, from different species (CASTRO et al, 2016;CHMELAŘ et al, 2016;KOTSYFAKIS et al, 2015;PERNER et al, 2016;RIBEIRO et al 2017;SCHWARZ et al, 2014;VALENZUELA, 2004;XU et al, 2016).…”
Section: Introductionmentioning
confidence: 99%